Corrosion and Stress Corrosion Testing of Aerospace Vehicle Structural Alloys - Wanhill, Russell (SpringerBriefs in Applied Sciences and Technology,, 2018)
This SpringerBrief discusses the determination and classification of the ambient temperature corrosion and stress corrosion properties of aerospace structural alloys, with emphasis on (1) aluminium alloys, modern (3rd generation) aluminium‒lithium alloys, stainless steels and titanium alloys and (2) some of the issues involved. Standard /reference data on environmental properties, including corrosion and stress corrosion, are mandatory for the qualification and certification of materials for aerospace vehicles, and also for the design of actual structures and components. Recommendations for further testing and evaluation are given at appropriate points in the text. The book concludes with a summary of the main topics. .